2012
DOI: 10.3346/jkms.2012.27.2.177
|View full text |Cite
|
Sign up to set email alerts
|

The Ability of β-Cells to Compensate for Insulin Resistance is Restored with a Reduction in Excess Growth Hormone in Korean Acromegalic Patients

Abstract: The aim of this study was to assess the prevalence of diabetes and to study the effects of excess growth hormone (GH) on insulin sensitivity and β-cell function in Korean acromegalic patients. One hundred and eighty-four acromegalic patients were analyzed to assess the prevalence of diabetes, and 52 naïve acromegalic patients were enrolled in order to analyze insulin sensitivity and insulin secretion. Patients underwent a 75 g oral glucose tolerance test with measurements of GH, glucose, insulin, and C-peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
(34 reference statements)
2
6
0
Order By: Relevance
“…In this study, prediabetes and DM were identified in 41 % and 34 % of the patients and these frequencies are compatible with the previous results reported in the literature [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. However frequency of DM was two-fold higher and prediabetes was slightly increased compared to the general Turkish population [30] and in accordance with many studies from several other countries [4-6, 8, 9, 15, 31].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, prediabetes and DM were identified in 41 % and 34 % of the patients and these frequencies are compatible with the previous results reported in the literature [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. However frequency of DM was two-fold higher and prediabetes was slightly increased compared to the general Turkish population [30] and in accordance with many studies from several other countries [4-6, 8, 9, 15, 31].…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, in this study we also evaluated HOMA-β index and pancreatic β-cell dysfunction. HOMA-β levels were lower in prediabetes group compared to patients with NGT, however, there was no statistical significance similar with previous observations in the literature [9]. These results may be interpreted as declining pancreatic β-cell functions in prediabetes patients.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Growth hormone (GH) and glucocorticoids can block the actions of insulin, resulting in diabetes mellitus (1,4). There have been several studies regarding the mechanism of increased insulin resistance in acromegaly patients.…”
Section: Introductionmentioning
confidence: 99%